The Short-Wave Mystery - Dixon W. Franklin; Franklin W. Dixon (Canada Franklin W. Dixon, 1945)
follows Frank and Joe Hardy as they investigate a, crime wave involving stolen stuffed animals and, concurrently, assist their father, Fenton, in breaking up an industrial spy ring that uses coded shortwave radio signals to coordinate thefts, leading them to a climax in Northern Canada.
Keywords: investigating a theft ring that uses ham radio to coordinate industrial espionage. The investigation is characterized by the following actions and behaviors; resourcefulness, integrity, and the power of persistence in the face of adversity. The story demonstrates that young people can make a significant impact through curiosity and teamwork